PENGEMBANGAN MEDIA MEMORA BERBASIS GAME-BASED LEARNING PADA MATERI NORMA-NORMA DI MASYARAKAT DI SEKOLAH DASAR - Mulyawan, Rico; Anggraeni Dewi, Dinie; Hawa, Siti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was motivated by elementary school students' low understanding of social norms and the limited use of innovative learning media in Pancasila Education learning. The study aimed to develop MEMORA (Norm Monopoly Media), determine its feasibility, and identify teachers' and students' responses to its use. This research employed the Design and Development (D&D) method using the ADDIE development model, which consists of the analysis, design, development, implementation, and evaluation stages. The research subjects included media experts, material experts, a fifth-grade teacher, and fifth-grade students at the Laboratory Elementary School of Universitas Pendidikan Indonesia (UPI) Cibiru Campus. Data were collected through interviews, questionnaires, and documentation. The findings revealed that MEMORA obtained a validation score of 90.38% from media experts and 92.31% from material experts, with an average score of 91.35%, categorized as highly feasible. The teacher response score reached 98%, while the students' response score was 93.8%, both categorized as highly feasible. These findings indicate that MEMORA is feasible and practical to be used as an alternative learning medium in Pancasila Education, particularly for teaching social norms, and has the potential to enhance students' engagement in the learning process.